Pengaruh Kompetensi Manajerial, Kewirausahaan, dan Promosi terhadap Kinerja Lembaga Kursus di Kota Pekanbaru - Resmita, Nila -; Sudjanto, Bedjo; Matin, Matin (JERAM, 2017)
The purpose of this research is to study the effect of managerial competence, entrepreneurship and promotion on performance of course institutions in Pekanbaru City. This research uses quantitative approach with survey method. The population in this research are 97 managers from course institutions in Pekanbaru City. The results of this research indicate that; (1) There is direct positive influence of managerial competence on course institutions performance; (2) There is direct positive influence of entrepreneurship on course institutions performance; (3) There is direct positive influence of promotion on course institutions performance; (4) Therefore, institutions’ performance improvement can be achieved well if there is strong influence from managerial competence, entrepreneurship, and promotion.